Launching cosmic-ray-driven outflows from the magnetized interstellar medium - Girichidis, Philipp; Naab, Thorsten; Walch, Stefanie; Hanasz, Michal; Mac Low, Mordecai-Mark; Ostriker, Jeremiah P.; Gatto, Andrea; Peters, Thomas; Wünsch, Richard; Glover, Simon; Klessen, Ralf S.; Clark, Paul C.; et al. (The astrophysical journal. Part 2, Letters, 2016)
We present a hydrodynamical simulation of the turbulent, magnetized, supernova (SN)-driven interstellar medium (ISM) in a stratified box that dynamically couples the injection and evolution of cosmic rays (CRs) and a self-consistent evolution of the chemical composition. CRs are treated as a relativistic fluid in the advection-diffusion approximation. The thermodynamic evolution of the gas is computed using a chemical network that follows the abundances of H+, H, H2, CO, C+, and free electrons and includes (self-)shielding of the gas and dust. We find that CRs perceptibly thicken the disk with the heights of 90% (70%) enclosed mass reaching ~1.5 kpc (~0.2 kpc). The simulations indicate that CRs alone can launch and sustain strong outflows of atomic and ionized gas with mass loading factors of order unity, even in solar neighborhood conditions and with a CR energy injection per SN of 10^50 erg, 10% of the fiducial thermal energy of an SN. The CR-driven outflows have moderate launching velocities close to the midplane (~100 km/s) and are denser (ρ~1e-24 - 1e-26 g/cm^3), smoother, and colder than the (thermal) SN-driven winds. The simulations support the importance of CRs for setting the vertical structure of the disk as well as the driving of winds.
Gesehen am 10.06.2020